The double-edged sword effects of active social media use on loneliness: The roles of interpersonal satisfaction and fear of missing out - Mao, Jian; Fu, Ge-xi; Huang, Jian-jun (Frontiers in Psychology, 2023)
This study explored the mechanism of the double-edged sword effect of active social media use (ASMU) on loneliness. A total of 454 college social media users completed an online questionnaire. The results of structural equation modeling indicated no significant direct association between ASMU and loneliness. Interpersonal relationship satisfaction and fear of missing out (FoMO) explained the different relationships between ASMU and loneliness. On the one hand, ASMU was associated with increased interpersonal satisfaction, which in turn negatively predicted loneliness; interpersonal satisfaction also reduced loneliness by decreasing general trait-FoMO. On the other hand, ASMU was also associated with an increase in online-specific state-FoMO, which positively predicted trait-FoMO, leading to an increase in loneliness. The above results contribute to dialectically understanding the effectiveness of active social media use and provide theoretical guidance for promoting the beneficial aspects of social media while weakening its harmful consequences.